P-C2 Characterization of the early antibody landscape in HIV-1 infected individuals who develop poor to elite levels of neutralization breadth. (March 2017) - Smith, S. Abigail; Burton, Samantha; Kilembe, William; Lakhi, Shabir; Karita, Etienne; Price, Matt; Allen, Susan; Hunter, Eric; Derdeyn, Cynthia
Abstract : Coevolution of HIV-1 envelope (Env) glycoproteins with the host antibody (Ab) response is a complex, dynamic process. Both are subject to high levels of mutation, either via error-prone reverse transcriptase in Env or somatic hypermutation (SHM) in Ab. And, while Env is subject to selection by neutralizing Ab (nAb), Env-specific B cells must compete with one another for antigen binding and survival signals. This evolutionary race results in the development of broadly neutralizing antibody (bnAb) activity in some patients, but not others. The coevolutionary path between Env and an autologous bnAb lineage has been explored in a few individuals. We have performed a more comprehensive characterization of the early anti-Env Ab landscape in individuals with varied levels of bnAb, on the premise that these responses are more comparable to Abs that can be elicited by vaccination. We have recovered ∼200 anti-Env- gp120 monoclonal antibodies (mAbs) from 6 individuals enrolled in IAVI Protocol C ∼7 months post-infection. These individuals display a range of neutralization breadth ∼3 years post-infection, from poor to elite. mAbs were characterized by analyzing the DNA sequences of immunoglobulin heavy (VH) and light (VL) chain variable domains, ability to neutralize autologous transmitted/founder (T/F) Env, and binding affinity (KD) for the T/F gp 120. Each individual exhibited a unique VH and VL germline landscape. Induction of bnAb-associated germlines, a high level of SHM, or long CDR-H3s was not predictive of bnAb development. Very high affinity early mAbs were associated with poor nAb breadth. Our studies reveal that premature induction of a clonal, VH-biased Ab response, with early acquisition of high KD, could be detrimental to the development of bnAb. Instead, induction and maturation of a bnAb lineage may initially require balanced VH germline usage, followed by substantial interplay between Env and Ab, to steadily increase affinity and drive acquisition of breadth.